2016
DOI: 10.1371/journal.pone.0150621
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Anticholinergic Burden and Adverse Health Outcomes in Parkinson Disease

Abstract: BackgroundElderly adults should avoid medications with anticholinergic effects since they may increase the risk of adverse events, including falls, delirium, and cognitive impairment. However, data on anticholinergic burden are limited in subpopulations, such as individuals with Parkinson disease (PD). The objective of this study was to determine whether anticholinergic burden was associated with adverse outcomes in a PD inpatient population.MethodsUsing the Cerner Health Facts® database, we retrospectively ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 66 publications
3
95
1
1
Order By: Relevance
“…There is also a high rate of use of anticholinergic drugs in many Asian countries for PD. Anticholinergics may aggravate cognitive decline and their role therefore needs to be examined [53]. …”
Section: Discussionmentioning
confidence: 99%
“…There is also a high rate of use of anticholinergic drugs in many Asian countries for PD. Anticholinergics may aggravate cognitive decline and their role therefore needs to be examined [53]. …”
Section: Discussionmentioning
confidence: 99%
“…Regarding anticholinergic use in particular, it has been demonstrated that the anticholinergic burden in patients with PD correlates with poor outcomes. A study in the United States demonstrated that higher anticholinergic use was associated with an increased risk of fractures, delirium, emergency department visits, and readmissions to the hospital . Furthermore, a recent study demonstrated that PD patients with a high cumulative dose of anticholinergics had an increased risk of being diagnosed with dementia .…”
Section: Discussionmentioning
confidence: 99%
“…Although the most recent study did not demonstrate disease‐modifying effect of the earlier initiation of levodopa, there was also no deleterious effect . Furthermore, recent work has demonstrated risks with the use of anticholinergic medications …”
mentioning
confidence: 99%
“…There is limited previous research on anticholinergic drug use in specific populations. Anticholinergic drug use has been evaluated, for example in persons with cognitive impairment, schizophrenia and Parkinson’s disease . There are a few previous studies investigating anticholinergic drug use in persons with diabetes .…”
Section: What Is Known and Objectivementioning
confidence: 99%